THE USE OF COAL AS FUEL FOR CEMENT MANUFACTURING AT PT. SEMEN GRESIK - Sumarwanto Sumarwanto (Testing Center for Oil and Gas LEMIGAS, 1991)
The conversion of fuel type, from oil to coal has considerable consequence as coal has very different combustion characteristics from oil. As the price of coalnis much lower, the process is viable.The use of coal as fuel in the cement industry requires more effort in technological treatment, such as: installationof the grinding plant, modification of the existing equipment, and the monitoring and continuous adjusting the blend. As the â€œashâ€ in the coal used for firing will combine with the raw mix during burning and thus causes a quite considerable change in the composition of the clinker. The combination of different blends of coal with different ash contents has to be carefully monitored to ensure clinker quality.